IMPROVEMENT OF POETRY WRITING SKILL THROUGH AUDITORY, INTELLECTUALLY, REPETITION (AIR) BASED ON OUTDOOR STUDY (Classroom Action Research of Third Grade at SD Negeri Soropadan No. 108 Surakarta Academic Year 2017/2018) - Proborini Proborini; Retno Winarni; Lies Lestari (Universitas Sebelas Maret, 2018)
The aim of this research to improve poetry writing skill through Auditory, Intellectually, Repetition (AIR) based on Outdoor Study for third grade students at SD Negeri Soropadan 108 Surakarta academic year 2017/2018. This research form was Classroom Action Research. It conducted by two cycles. Each cycle consist of planning, acting, observing, and reflecting. Data collection technique used interview, observation, test, and documentation. Data validity technique used content validity, resources triangulation, and technique triangulation. Data analysis technique consisted by data collection, data reduction, data display, and conclusion. The result of this research indicated improvement of poetry writing skill of third grade students at SD Negeri Soropadan 108 Surakarta academic year 2017/2018 from preaction 29,73%, cycle I 54,05%, and cycle II 89,19%. The conclusion of this research indicated that through Auditory, Intellectually, Repetition (AIR) based on Outdoor Study can improve student writing skill of third grade students at SD Negeri Soropadan 108Surakarta academic year 2017/2018.